Effects of severe scoliosis on cardiac structure and function in resting patients: a retrospective study - Jie Xiao; Tao Li; Yingsong Wang; Zhi Zhao; Jingming Xie; Jin Zhou (Journal of Orthopaedic Surgery and Research)
Abstract Background Severe scoliosis may impair cardiac structure and function. This study aims to evaluate the cardiac structural and functional changes in patients with severe thoracic scoliosis at rest, using echocardiography to inform perioperative strategies. Methods This retrospective cohort analysis included 294 patients with idiopathic scoliosis (IS) characterized by primary thoracic curvature and no history of previous spinal surgery. The study included 97 patients with severe scoliosis (defined as a Cobb angle ≥ 90°) and 197 patients with a Cobb angle < 90°, who were categorized as Non-severe scoliosis. General data, including age, gender, height, weight, BMI, and primary thoracic curve characteristics, were collected for all patients. Subgroup analyses were conducted based on age, gender, Cobb angle, and curve direction. Cardiac metrics, including structural and functional parameters, were compared, and correlations between Cobb angle and cardiac indicators in severe scoliosis were assessed. Results Patients with severe scoliosis exhibited significantly reduced cardiac parameters, including left ventricular diastolic diameter (LVDd), right ventricular diastolic diameter (RVDd), interventricular septal thickness (IVST), left ventricular posterior wall thickness (LVPWT), ejection fraction (EF), and fractional shortening (FS) (p < 0.05). Subgroup analysis revealed lower LVDd and cardiac index (CI) in patients with Cobb angles ≥ 120° compared to 90–120° (p < 0.05). The direction of the thoracic curve did not significantly impact cardiac structure or function (p > 0.05). Patients older than 18 years had significantly larger cardiac structural parameters than younger patients, although cardiac function remained similar. Male patients exhibited greater right heart dimensions compared to females. Correlation analysis demonstrated a negative association between Cobb angle and LVDd and CI (p < 0.05). Conclusions Severe thoracic scoliosis significantly affects cardiac structure and function at rest, primarily impacting left ventricular dimensions and cardiac index. Age and gender influence specific cardiac structural parameters but have a limited impact on cardiac function. Preoperative assessments should prioritize LVDd and CI for a thorough evaluation of cardiac health in these patients. The direction of the primary thoracic curve does not significantly influence cardiac structure or function. The severity of the spinal deformity, rather than the curvature direction, is the main determinant of its impact on cardiac health.